2015
DOI: 10.1093/bioinformatics/btv076
|View full text |Cite
|
Sign up to set email alerts
|

Application of clinical text data for phenome-wide association studies (PheWASs)

Abstract: As an alternative to ICD9 coding, a text-based phenome was defined by 23 384 clinically relevant terms extracted from Marshfield Clinic's EHR. Five single nucleotide polymorphisms (SNPs) with known phenotypic associations were genotyped in 4235 individuals and associated across the text-based phenome. All five SNPs genotyped were associated with expected terms (P<0.02), most at or near the top of their respective PheWAS ranking. Raw association results indicate that text data performed equivalently to ICD9 cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…In the first demonstration of the value of EHR text data, Hebbring et al (27) identified 23,384 one- to four-word phrases occurring in clinical narratives that matched to medical concepts in the UMLS. In this approach, which they called a TextWAS, they replicated known associations for five SNPs with similar performance to using ICD9 codes for these diseases.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the first demonstration of the value of EHR text data, Hebbring et al (27) identified 23,384 one- to four-word phrases occurring in clinical narratives that matched to medical concepts in the UMLS. In this approach, which they called a TextWAS, they replicated known associations for five SNPs with similar performance to using ICD9 codes for these diseases.…”
Section: Future Directionsmentioning
confidence: 99%
“…Using automated phenotyping algorithms, investigators have identified cases and controls for diseases of interest to replicate known phenotype-genotype associations and make novel discoveries, [12][13][14][15][16][17] potentially with decreased cost 18 and faster execution than traditional trials.…”
Section: Background and Significancementioning
confidence: 99%
“…Based on ICD9 codes to define cases and controls [2931], no phenotype passed a conservative Bonferroni threshold (p<7.2E-6, assuming α < 0.05 and 6910 tests/phenotypes). The top associations included ICD9 616.3 defining abscess of Bartholin’s gland (p= 0.00020, OR=2.0[1.4–2.9]) followed by ICD9 379.92 defining swelling or mass of eye (p= 0.00021, OR=1.7[1.3–2.3]) (Figure 2, Supplementary Table 2); the relevance of these association is uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The phenome was defined by ICD9 coding extracted from patient EHR data using standard methods as described previously [2931]. Individuals whose medical records contained ICD9 codes inclusive of three levels of resolution defined by ICD9 code suffix (for example, ICD9 720, 720.8, 720.89) were designated as a case for a particular condition, whereas individuals with no record of the broadest code (e.g., 720) were classified as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation